O PIBID diversidade na escola Professor Basílio de Carvalho: uma análise a partir do olhar da equipe gestora - MORAES, Danrley Ferreira (2019)
The present work of course conclusion emerged from my experience as a scholarship holder of the Institutional Scholarship Program of the Teaching Initiation / Abaetetuba Subproject - PIBID Diversity and presents the following research question: what is the contribution of PIBID Diversity in the process of teaching and learning of the students of the field, from the conception of the managers of the school Professor Basílio de Carvalho? It has as general objective to analyze the contribution of the PIBID Diversity in the teaching and learning process of the students of the field, from the speeches of the managers of a school of the field of the municipality of Abaetetuba / PA and as specific objectives: I- To point out the contributions of the PIBID in the pedagogical work of teachers and managers; II- Analyze the teaching and learning activities developed by PIBID scholarship holders Diversity in the classroom with students coming from island communities and roads; III- Understand the contributions of PIBID Diversity for the teaching and learning process from the speeches of the managers interviewed. The program has an important role in schools, however, it seeks to understand how managers evaluate the presence of PIBID in them, in the case of the rural schools the PIBID Diversity. For the purposes of this research, a qualitative approach was used, according to studies by Gonçalves et al (2014) and semi-structured interviews as described by Minayo (2002). Based on this, prior interviews were conducted with the target audience to obtain the data, according to the participants' availability. With the information obtained, it was concluded that through the didactic and pedagogical workshops, the scholarship holders contribute to soften the difficulties of the students, mainly in the subjects of mathematics and Portuguese language, carried out in a playful way, leaving a little of the routine of traditional teaching. In this context, through the interviewees' speeches, it was identified that the PIBID Diversity contributed to the school and to the students, especially in moments where there were no teachers to comply with the class schedule.